Mass balance modeling for electric arc furnace and ladle furnace system in steelmaking facility in turkey - (:unkn) unknown (SPRINGER, 2007)
In the electric arc furnace (EAF) steel. production processes, scrap steel is principally used as a raw material instead of iron ore. In the steelmaking process with EAF, scrap is first melted in the furnace and then the desired chemical composition of the steel can be obtained in a special furnace such as ladle furnace (LF). This kind of furnace process is used for the secondary refining of alloy steel. LF furnace offers strong heating fluxes and enables precise temperature control, thereby allowing for the addition of desired amounts of various alloying elements. It also provides outstanding desulfurization at high-temperature treatment by reducing molten steel fluxes and removing deoxidation products. Elemental analysis with mass balance modeling is important to know the precise amount of required alloys for the LF input with respect to scrap composition. In present study, chemical reactions with mass conservation law in EAF and LF were modeled altogether as a whole system and chemical compositions of the final steel alloy output can be obtained precisely according to different scrap compositions, alloying elements ratios, and other input amounts. Besides, it was found that the mass efficiency for iron element in the system is 95. 93%. These efficiencies are calculated for all input elements as 8. 45 % for C, 30. 31 Yo for Si, 46. 36 % for Mn, 30. 64 Yo for P, 41. 96 Yo for S, and 69. 79% for Cr, etc. These efficiencies provide valuable ideas about the amount of the input materials that are vanished or combusted for 100 kg of each of the input materials in the EAF and LF system.
Keywords: electric arc furnace; ladle furnace; system modeling; mass balance; steelmaking; liquid steel